(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
We studied the change in blood lipidemic parameters under the influence of casein hydrolysates obtained under the influence of gastric and pancreatic juices. The study was carried out in chronic experiments on dogs. It was concluded that casein hydrolysates obtained under the influence of gastric juice contribute to the improvement of digestion and absorption of fats. Casein hydrolysates, obtained under the influence of pancreatic juice, help to reduce the digestion and absorption of fats. The effects of the influence of casein hydrolysates on lipidemic blood parameters depend on which proteases under the influence of casein hydrolysates are obtained, and also, possibly, on the sequence of action of proteases on casein when hydrolysates and peptides are obtained from it.